THE INFLUENCE OF CONTEMPORARY MUSICAL INSTRUMENTS MEDIA ON THE LEARNING OUTCOMES OF CULTURAL ARTS OF GRADE V SD IT AL-MANAR MEDAN - Arrini Shabrina Anshor (West Science Interdisciplinary Studies, 2023)
This study aims to determine whether there is influence of contemporary musical instrument media on the learning outcomes of Cultural Arts class V SD IT Al-Manar Medan. The research method used is quantitative with a quasi-experimental design approach. As for the sample in this study, there were 12 students in class V SD, which were divided into 2 groups consisting of 6 students in the experimental class and 6 students in the control class. The instrument used is a test sheet. Data collection techniques in this study used test techniques and documentation techniques. Based on the research results from the results of tests by researchers by filling out test sheets, based on the results of the study it can be concluded that contemporary musical instrument media has an effect on music learning outcomes. The research will be conducted for 1 (one) year. This research is a research in the field of focus on Art Education. The mandatory achievement targets or outcomes of this research are one article in an accredited national journal and one article in the proceedings of a national seminar.